2020
DOI: 10.1080/07317115.2020.1836106
|View full text |Cite
|
Sign up to set email alerts
|

Could Frailty be an Explanatory Factor of the Association between Depression and Other Geriatric Syndromes in Later Life?

Abstract: Objectives: This study aimed to investigate whether frailty could be an explanatory factor of the association between depression and the number of geriatric syndromes. Methods: Cross-sectional baseline data from a cohort study (MiMiCS-FRAIL) were analyzed in a sample of 315 older adults. Depression was measured according to DSM-5 criteria and a selfreport questionnaire (PHQ-9). Frailty was assessed according to the FRAIL questionnaire and a 30item Frailty Index (FI). We considered six geriatric syndromes. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
10
0
4
Order By: Relevance
“…GDS-15 and PHQ-9) do not immediately lead to a diagnosis but can accurately identify patients who are at risk. In addition, our findings can contribute with the assessment of depressive symptoms that seem to yield similar and good results (32,33). These results could be explained by findings that depressive symptoms were associated with an increased risk for frailty (OR = 2.20, [95% CI = 1.88-2.57]) over 3-years follow-up (48).…”
Section: Main Findingsmentioning
confidence: 57%
See 3 more Smart Citations
“…GDS-15 and PHQ-9) do not immediately lead to a diagnosis but can accurately identify patients who are at risk. In addition, our findings can contribute with the assessment of depressive symptoms that seem to yield similar and good results (32,33). These results could be explained by findings that depressive symptoms were associated with an increased risk for frailty (OR = 2.20, [95% CI = 1.88-2.57]) over 3-years follow-up (48).…”
Section: Main Findingsmentioning
confidence: 57%
“…Eligible participants of the MiMiCS-FRAIL are all new referrals to the clinic (from general practitioners or patient's direct access) aged 60 years or over, with regular clinical appointment and follow-up (at least one visit to the clinic every 12 months). Exclusion criteria are: All included participants had a baseline assessment with a comprehensive geriatric assessment (CGA) protocol including a structured diagnostic interview, a complete physical and psychiatric evaluation and validated self-report questionnaires with a team of geriatricians, psychiatrists and physical therapists (32)(33)(34). Subsequently, patients are routinely followed-up every 12 months (at least) with the CGA.…”
Section: Study Design Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Frailty and multimorbidity are common and major age-related clinical syndromes and well-established independent risk factors for psychological health in older people [6][7][8]. Separate studies have reported that frailty or multimorbidity can independently increase the levels of psychological distress in older people [7,9,10]. However, an individual can be multimorbid but not frail or frail while having multimorbidity.…”
Section: Introductionmentioning
confidence: 99%